Impacts of dust events on chemical characterization and associated source contributions of atmospheric particulate matter in northern China. (1st January 2023) - Li, Ruiyu; Zhang, Miao; Du, Yuming; Wang, Guixia; Shang, Chunlin; Liu, Yao; Zhang, Min; Meng, Qingpeng; Cui, Min; Yan, Caiqing
Abstract: Sand and dust have significant impacts on air quality, climate, and human health. To investigate the influences of dust storms on chemical characterization and source contributions of fine particulate matter (PM2.5 ) in areas with different distances from dust source regions, PM2.5 and associated chemical composition were measured in two industrial cities with one near sand sources (i.e., Wuhai) and the other far from sand sources (i.e., Jinan) in northern China in March 2021. Results showed that PM mass concentrations significantly increased and exceeded the Chinese National Ambient Air Quality standard during the dust events, with absolute concentrations and fractional contributions of PM2.5 -bound crustal and trace elements increased while secondary inorganic ions decreased at both sites. Crustal materials dominated the increased PM2.5 mass from non-dust period to dust period in both cities. These were further evidenced by PM2.5 source apportionment results from positive matrix factorization model. During the dust events, dust sources contributed up to 88% of PM2.5 mass in Wuhai and ∼38% of PM2.5 mass in Jinan, a city about thousands of kilometers away from the sand source. Besides, the measurement data indicated that dust from northwest China may also bring along with high abundance of organic matter and vanadium. Secondary and traffic sources were two of the most important source contributors to PM2.5 in both cities during the non-dust periods. However, the near sand source city was more susceptible to the aggravating effects of dust and minerals, with much higher contributions by crustal materials (∼47%, from the aspect of chemical components) and dust-related sources (∼26%, from the aspect of sources) to PM2.5 mass even during non-dust periods. This study highlighted the urgent need for more action and effective control of sand sources to reduce the impact on air quality in downstream regions. Graphical abstract: Image 1 Highlights: Particle-bound elements increased significantly during dust events at both sites. Absolute and relative contributions of secondary ions decreased during dust events. Dust related source contributions remarkably increased during dust events. Areas near the sand source are more susceptible to the effects of sand and dust.